Effect of X-ray minibeam radiation therapy on clonogenic survival of glioma cells. (November 2018) - Guardiola, Consuelo; Prezado, Yolanda; Roulin, Christophe; Bergs, Judith W.J.
Highlights: First in vitro study performed in an X-ray SARRP for minibeam irradiations. At equal mean dose, the same tumor control can be obtained with standard and minibeam irradiations. This contradicts the established paradigms of the standard radiation therapy. Abstract: The goal is to compare, in vitro, the efficiency of minibeam radiotherapy (MBRT) and standard RT in inducing clonogenic cell death in glioma cell lines. With this aim, we report on the first in vitro study performed in an X-ray Small Animal Radiation Research Platform (SARRP) modified for minibeam irradiations. F98 rat and U87 human glioma cells were irradiated with either an array of minibeams (MB) or with conventional homogeneous beams (broad beam, BB). A specially designed multislit collimator was used to generate the minibeams with a width of a center-to-center distance of 1465 (±10) μm, and a PVDR value of 12.4 (±2.3) measured at 1 cm depth in a water phantom. Cells were either replated for clonogenic assay directly (immediate plating, IP) or 24 h after irradiation (delayed plating, DP) to assess the effect of potentially lethal damage repair (PLDR) on cell survival. Our hypothesis is that with MBRT, a similar level of clonogenic cell death can be reached compared to standard RT, when using equal mean radiation doses. To prove this, we performed dose escalations to determine the minimum integrated dose needed to reach a similar level of clonogenic cell death for both treatments. We show that this minimum dose can vary per cell line: in F98 cells a dose of 19 Gy was needed to obtain similar levels of clonogenic survival, whereas in U87 cells there was still a slightly increased survival with MB compared to BB 19 Gy treatment. The results suggest also an impairment of DNA damage repair in F98 cells as there is no difference in clonogenic cell survival between immediately and delayed plated cells for each dose and irradiation mode. For U87 cells, a small IP-DP effect was observed in the case of BB irradiation up to a dose of 17 Gy. However, at 19 Gy BB, as well as for the complete dose range of MB irradiation, U87 cells did not show a difference in clonogenic survival between IP and DP. We therefore speculate that MBRT might influence PLDR. The current results show that X-ray MBRT is a promising method for treatment of gliomas: future preclinical and clinical studies should aim at reaching a minimum radiation (valley) dose for effective eradication of gliomas with increased sparing of normal tissues compared to standard RT.